Comparison of center of pressure trajectory characteristics in table tennis during topspin forehand loop between superior and intermediate players - Fu, F.; Zhang, Y.; Shao, S.; Ren, J.; Lake, M.; Gu, Y. (International Journal of Sports Science & Coaching, 2016)
The purpose of this study was to investigate the characteristics of center of pressure (COP) trajectory during table tennis topspin forehand loop between superior and intermediate players. Twenty-six male table tennis players with two different skilled level participated in this test. Novel Pedar insole plantar pressure measurement system was used to record COP displacement. Subjects were asked to perform crosscourt forehand loop against the topspin ball with maximal power. The motion was divided into two phases as backswing and forward swing. Compared to intermediate players, superior players showed significantly larger medial-lateral COP displacement at backward-end and significantly smaller anterior-posterior displacement at both backward and forward ends. In addition, the ratio of COP velocity between forward swing and backswing was much higher for superior subjects. Results indicated that superior players possessed better foot drive technique and ability of foot motion control during forehand loop. These characteristics are beneficial for coaches to develop special training schemes in improving forehand loop performance. ABSTRACT FROM AUTHOR